Unveiling the challenges: exploring start-up hurdles faced by small and medium-sized enterprise entrepreneurs in Sri Lanka - Amila Gankandage; Ruwan Jayathilaka (Humanities & Social Sciences Communications)
Abstract This study specifically focuses on the factors contributing to start-up failures in the SME sector in Sri Lanka, with particular emphasis on the educational, socio-cultural, economic, and psychological variables that affect entrepreneurial outcomes. The primary objective is to identify and analyse the factors contributing to these failures. Data collection involved interviews, telephone surveys, and online questionnaires. Given that the dependent variable categorises outcomes as either success or failure, a Probit regression model, was deemed the most appropriate analytical method. The findings reveal significant impacts of educational and economic factors on start-up failures in the SME sector. Additionally, psychological, and socio-cultural factors were found to influence these failures. Most participants recommended integrating entrepreneurship and skill development topics into the O/Level and A/Level curricula. Based on these insights, this study proposes several policy recommendations. It suggests that policymakers improve the education system to meet the country’s educational needs more effectively. It also recommends that family members, society, and religious leaders receive education pertaining to start-up development. Furthermore, it advises policymakers and financial institutions to align more closely with entrepreneurial needs to prevent business failures. Lastly, the study emphasises the importance of educating entrepreneurs on maintaining a motivated and positive attitude, addressing the fear of loss, and understanding the psychological aspects of business management. Building upon the brief overview in the abstract, the following introduction lays the foundation for our study, elaborating on the economic concepts and contextual background.